Conservation of rare and endangered plant species in China - Yue Xu; Runguo Zang (iScience, 2023)
Summary: Rare and endangered plant species (REPs) are facing high danger of extinction, yet a comprehensive and up-to-date review on their conservation in China is still lacking. This paper systematically collected studies and achievements on REPs conservation, including species surveys and monitoring, cause of endangerment, in situ conservation, ex situ conservation, reintroduction, propagation, conservation legislation, public participation, progress in conservation of wild plant with extremely small populations, and progress in China’s implementation of the Convention on Biological Diversity. Although enormous advances have been made in conservation policies and legislations, protection systems, and research, as well as public education and international collaborations, the conservation efficiency is still restricted largely by the conflict between economic growth and biodiversity conservation in China. In order to meet its commitments to the new Post-2020 Global Biodiversity Framework, more work on basic investigation and long-term observation, as well as advanced technologies and application-oriented research on REPs should be carried out.